2009
DOI: 10.1186/1471-2334-9-18
|View full text |Cite
|
Sign up to set email alerts
|

Using high titer West Nile intravenous immunoglobulin from selected Israeli donors for treatment of West Nile virus infection

Abstract: BackgroundWest Nile Virus (WNV) is endemic in Israel and a significant level of antibodies is present in the population due to natural exposure. Anecdotal cases suggested that the presence of anti-WNV antibodies in intravenous immunoglobulin (IVIG) from Israeli donors (IVIG-IL) assisted the recovery of patients with severe WNV infection.MethodsTo enhance the therapeutic efficacy of IVIG-IL against WNV infection, OMRIX Biopharmaceuticals, Israel, have developed a strategy for selection of plasma units from a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 34 publications
0
52
0
1
Order By: Relevance
“…We previously showed that IVIG could temper CNS infiltration by pathogenic Ly6C high monocytes and Ly6G + neutrophils, and thereby protect mice from lethal HSV1 encephalitis (Ramakrishna et al, 2011). Additionally, earlier studies showed that high titrated IVIG collected from WNV endemic areas, but not non-immune IVIG, was protective in mouse WNV challenge studies when given at low doses (0.1-0.6 g kg 21 ) (Ben-Nathan et al, 2009;. To determine the therapeutic potential of generic IVIG as an anti-inflammatory agent, we investigated the effects of high-dose (¢1 g kg 21 ) and lowdose (160 mg kg 21 ) IVIG on the development of WNV encephalitis.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that IVIG could temper CNS infiltration by pathogenic Ly6C high monocytes and Ly6G + neutrophils, and thereby protect mice from lethal HSV1 encephalitis (Ramakrishna et al, 2011). Additionally, earlier studies showed that high titrated IVIG collected from WNV endemic areas, but not non-immune IVIG, was protective in mouse WNV challenge studies when given at low doses (0.1-0.6 g kg 21 ) (Ben-Nathan et al, 2009;. To determine the therapeutic potential of generic IVIG as an anti-inflammatory agent, we investigated the effects of high-dose (¢1 g kg 21 ) and lowdose (160 mg kg 21 ) IVIG on the development of WNV encephalitis.…”
Section: Resultsmentioning
confidence: 99%
“…When a virus or microbial agent is expanding its geographical range, exposure of the formerly naïve population to this novel agent is reflected in the Ab content of IVIG. This was demonstrated, e.g., for US-IVIG after the introduction of WNV into the United States in 1999 (4,25,31) and recently also for EU-IVIG, where increasing WNV-neutralizing Ab titers were detected in EU-IVIG lots manufactured after 2009, even though no human WNV infections have yet been reported from the countries in which the plasma was sourced (31).To further increase the understanding of the geographical difference in IVIG Ab content, we determined the neutralizing Ab titers of IVIG preparations for tick-borne encephalitis virus (TBEV). This member of the Flaviviridae, for which three subtypes (European, Siberian, and Far Eastern) are distinguished, may cause tick-borne encephalitis (TBE), a potentially serious neurological disease with high fever and encephalitis (33), while 70 to 95% of human infections in regions in which the virus is endemic are either subclinical or totally asymptomatic (12).…”
mentioning
confidence: 99%
“…When a virus or microbial agent is expanding its geographical range, exposure of the formerly naïve population to this novel agent is reflected in the Ab content of IVIG. This was demonstrated, e.g., for US-IVIG after the introduction of WNV into the United States in 1999 (4,25,31) and recently also for EU-IVIG, where increasing WNV-neutralizing Ab titers were detected in EU-IVIG lots manufactured after 2009, even though no human WNV infections have yet been reported from the countries in which the plasma was sourced (31).…”
mentioning
confidence: 99%
“…Moreover, partially mature flavivirus virions containing some uncleaved prM also retain infectivity (29,33,51 (22,74). Moreover, preexposure prophylaxis and postexposure therapy with WNV-specific monoclonal antibody (MAb) or polyclonal antibodies conferred protection in both mice and hamsters (6,7,22,48,53,71,74,75). The E protein of WNV is the principal target of neutralizing antibodies.…”
mentioning
confidence: 99%